2015
DOI: 10.1142/9789814730617_0011
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-Breaking and the Contextual Emergence of Human Multiagent Coordination and Social Activity

Abstract: Here we review a range of interpersonal and multiagent phenomena that demonstrate how the formal and conceptual principles of symmetry, and spontaneous and explicit symmetry-breaking, can be employed to investigate, understand, and model the lawful dynamics that underlie selforganized social action and behavioral coordination. In doing so, we provided a brief introduction to group theory and discuss how symmetry groups can be used to predict and explain the patterns of multiagent coordination that are possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Indeed, the emergence of collective behavior is often a direct consequence of human actors needing to realize task behaviors that are beyond the scope of their individual capabilities (Goldstone & Gureckis; 2009; Richardson et al, 2007). This implies that the performance ability of co-actors in relation to task difficulty reflects a generic control parameter that pushes individuals in and out of complementary and synchronous patterns of behavioral coordination (Richardson & Kallen, 2015, Roberts & Goldstone, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the emergence of collective behavior is often a direct consequence of human actors needing to realize task behaviors that are beyond the scope of their individual capabilities (Goldstone & Gureckis; 2009; Richardson et al, 2007). This implies that the performance ability of co-actors in relation to task difficulty reflects a generic control parameter that pushes individuals in and out of complementary and synchronous patterns of behavioral coordination (Richardson & Kallen, 2015, Roberts & Goldstone, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…In turn, a growing number of researchers have also argued that multiagent activity is best conceptualized as a complex dynamical system and, moreover, that the behavioral order of self-organized, synergistic multiagent coordination can be understood and modeled using low-dimensional task or behavioral dynamics principles (e.g., Schmidt et al, 1990, 1998; Warren, 2006; Lagarde, 2013; Dumas et al, 2014; Richardson and Kallen, 2015; Richardson et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…A foundational example of such behavioral dynamics modeling is provided by the work of Fajen and Warren [11], [13], [22], [23], in which the authors successfully modeled the self-organized behavioral dynamics of human locomotory navigation and route selection. Of particular relevance for the current study, is that extensions of this model have been demonstrated to characterize human hand movements in object moving and placing task [7], [16], [18], [24], [25]. In this context an agent's end effector (i.e.…”
Section: Behavioral Dynamicsmentioning
confidence: 99%
“…Similar navigation equations can be extended to a range of complex multi-agent locomotion or pedestrian tasks [14], [15] as well as a wide range of joint action and multi-agent movement coordination tasks [7], [16], [18], [24]. In the context of robotics it has been shown that this approach to individual path navigation results in a system that is capable of avoiding local minima within a navigation space [27] as well as is capable of successfully avoiding an arbitrary number of obstacles [27], [29].…”
Section: Behavioral Dynamicsmentioning
confidence: 99%